Comparison of tissue level of selenium and zinc in patients with nasal polyposis and healthy people - Soheila Nikakhlagh; Zahra Ramezani; Ayeh Kiani (Elsevier, 2021)
Background: Nasal polyposis (NP) is an inflammatory condition in nasal and paranasal sinus cavities and its pathophysiology is poorly understood. It seems likely that the trace elements such as zinc and selenium may play a critical role in the genesis of inflammatory sinonasal disease. Objectives: The aim of this study was to investigate the role of these elements in NP and compare these findings with normal nasal mucosa. Methods & materials: In this descriptive-analytic cross-sectional study which was done at Imam Khomeini hospital of Ahvaz between July 2018 and June 2019, selenium and zinc levels measured in polyp tissues of 72 patients (47 men and 25 women) and were compared with healthy nasal mucosa of 36 control cases (15 men and 21 women). Hydride generation and flame atom absorption spectroscopy were utilized for selenium and zinc quantifications, consequently. Results: The mean tissue zinc and selenium levels were, respectively, 18.569 μg/g and 68.65 ng/g in patients group and 71.015 μg/g, 249.53 ng/g in control group. It was found that the concentrations of zinc element were significantly lower in polyp tissues than healthy nasal mucosa. In the case of selenium no significant difference was found between patients and controls. Conclusion: Trace elements are undoubtedly useful, and further studies are needed to determine the effect of zinc and selenium on nasal and sinus polyps.